2021
DOI: 10.1523/jneurosci.2204-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

An Implanted Vestibular Prosthesis Improves Spatial Orientation in Animals with Severe Vestibular Damage

Abstract: Gravity is a pervasive environmental stimulus, and accurate graviception is required for optimal spatial orientation and postural stability. The primary graviceptors are the vestibular organs, which include angular velocity (semicircular canals) and linear acceleration (otolith organs) sensors. Graviception is degraded in patients with vestibular damage, resulting in spatial misperception and imbalance. Since minimal therapy is available for these patients, substantial effort has focused on developing a vestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…As expected, our static mapping generated VOR responses consistent with the results of these prior studies, which were characterized by poor phase compensation. Finally, it is noteworthy that prior work by Merfeld and colleagues employed a dynamic mapping between angular head velocity to a specific pulse rate [ 33 , 37 39 ]. However, this mapping only approximated afferent dynamics over a very low frequency range (<0.1 Hz) and thus performed in a comparable manner to the static mapping over most of the natural frequency range (i.e., 0.1 Hz to 20 Hz).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, our static mapping generated VOR responses consistent with the results of these prior studies, which were characterized by poor phase compensation. Finally, it is noteworthy that prior work by Merfeld and colleagues employed a dynamic mapping between angular head velocity to a specific pulse rate [ 33 , 37 39 ]. However, this mapping only approximated afferent dynamics over a very low frequency range (<0.1 Hz) and thus performed in a comparable manner to the static mapping over most of the natural frequency range (i.e., 0.1 Hz to 20 Hz).…”
Section: Discussionmentioning
confidence: 99%
“…This situation seems to induce a neurosensory conflict that causes plastic changes leading to a reduction of the gain of the afferent input from the SCC with critical functional consequences ( Kornilova and Kozlovskaya, 2003 ; Kornilova et al, 2017 ). Although, in monkeys with VI in the three SCC the brain may extract information about head position ( Karmali et al, 2021 ). Also in humans wearing the Geneva-Maastricht VI, acoustically elicited cervical vestibular evoked myogenic potentials (cVEMPs) can be elicited, suggesting that VI in SCC can improve postural control ( Perez-Fornos et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results also showed that head movements elicited by horizontal SCC stimulation significantly contributed to gaze stabilization, complementing the VOR ( Mitchell et al, 2013 ). It has also been shown in two rhesus monkeys that head orientation perception improves using a VI that stimulated the three SCC can improve graviception, indicating that the brain may extract information about the head’s orientation from the SCC activity ( Karmali et al, 2021 ).…”
Section: Implantable Vestibular Prosthesis (Animal Experiments)mentioning
confidence: 99%
“…Vestibular dysfunction and its precipitating factors (such as hearing loss; see recent Review Smith, 2021, vestibular migrane and vertigo) are at least partially modifiable [ 14 , 17 , 18 ]. Thus, identifying and treating early vestibular dysfunction may serve a preventative role in AD.…”
Section: Introductionmentioning
confidence: 99%